Computed tomographic dimensions of the normal adult equine eye. (4th February 2019) - Hollis, Anna R.; Dixon, Jonathon J.; Berlato, Davide; Murray, Rachel; Weller, Renate
Abstract: There are limited data on whether the dimensions of the equine eye and its internal structures change with bodyweight in horses. The aim of this study was to identify whether the size of the equine eye and its individual structures varied in a predictable manner with bodyweight, and to examine the reliability of computed tomography (CT) scans in the measurement of the equine eye. Ninety horses which had undergone CT examination of the head for non‐ocular disease were included. All measurements of the eye were performed twice on all eyes by the same operator to quantify intra‐operator agreement, and in 10 cases were also performed by a second operator to quantify inter‐operator agreement. Agreement was excellent for all but the rostrocaudal measurement of the anterior chamber, which was fair. The following variables correlated significantly with bodyweight: anterior‐posterior size of the globe (correlation coefficient: 0.586) and posterior segment (correlation coefficient: 0.554); the latero‐medial size of the globe (correlation coefficient: 0.452), anterior chamber (correlation coefficient: 0.504) and posterior segment (correlation coefficient: 0.455); and the orbital fossa diameter (correlation coefficient: 0.219). The lens size and anterior‐posterior distance of the anterior chamber did not correlate significantly with bodyweight. These results suggest that overall eye size and the size of the orbital fossa change with the bodyweight of the horse, but lens size remains consistent, and that CT measurements of the internal structures of the eye are repeatable and reproducible. This information aids in interventional procedures for ocular pathology and assessment of normal anatomy.